Feeding habit and length weight relationship of keureling fish, Tor tambra Valenciennes, 1842 (Cyprinidae) from the western region of Aceh Province, Indonesia - ZAINAL A. MUCHLISIN; AGUNG S. BATUBARA; MOHD N. SITI AZIZAH; MUHAMMAD ADLIM; AFRIZAL HENDRI; NUR FADLI; ABDULLAH A. MUHAMMADAR; SUGIANTO SUGIANTO (Society for Indonesian Biodiversity, 2015)
Muchlisin ZA, Batubara AS, Siti-Azizah MN, Adlim M, Hendri A, Fadli N, Muhammadar AA, Sugianto S. 20015. Feedinghabit and length weight relationship of keureling fish, Tor tambra Valenciennes, 1842 (Cyprinidae) from the western region of Aceh Province, Indonesia. Biodiversitas 16: 89-94. The objective of the present study was to describe the aspects of feeding habit and lengthweightrelationship of keureling fish Tor tambra, this information is crucial to plan a conservation startegy for this species. A series ofsamples were taken between June and September 2012 and February 2014 in the two main rivers of western Aceh i.e. the Sikundo andNagan Rivers. A total of 48 and 38 fish were caught during the study in Nagan and Sikundo Rivers, respectively. Stomach contentanalysis suggested that freshwater green algae and earthworms were the main food items for T. tambra, indicating an omnivorousfeeding habit. In addition, the length-weight relationship revealed that T. tambra has an allometric negative growth pattern from allpopulations, and the condition factors indicate the rivers are still in good condition and support fish life.